1998
DOI: 10.1093/nar/26.11.2827
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF mass spectrometric typing of single nucleotide polymorphisms with mass-tagged ddNTPs

Abstract: A matrix-assisted laser desorption/ionization time-of-flight mass spectrometry based method has recently been reported for the typing of single nucleotide polymorphisms using single nucleotide primer extension. This method is limited in some cases by the resolution of the mass determination, as the mass difference between nucleotides can be as little as 9 Da (the difference between A and T). A variation of this method is described here in which a mass-tagged dideoxynucleotide is employed in the primer extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 11 publications
(9 reference statements)
1
47
0
1
Order By: Relevance
“…To date, Tang et al [5] and Liu et al [6] have reported the analysis of PCR products ϳ500 to 600 bases using UV-MALDI (at 337/355 nm), and Hillenkamp and co-workers extended the upper limit of DNA and RNA analyses up to ϳ2180 bases using IR-MALDI [7]. Applications such as analyzing short tandem repeats [8], gene-defect diseases [9 -11], and genotyping of single nucleotide polymorphisms [12] have been attempted. Despite these successes, oligonucleotide analysis by MALDI-MS has been limited primarily by the low ion abundances of larger oligonucleotides.…”
mentioning
confidence: 99%
“…To date, Tang et al [5] and Liu et al [6] have reported the analysis of PCR products ϳ500 to 600 bases using UV-MALDI (at 337/355 nm), and Hillenkamp and co-workers extended the upper limit of DNA and RNA analyses up to ϳ2180 bases using IR-MALDI [7]. Applications such as analyzing short tandem repeats [8], gene-defect diseases [9 -11], and genotyping of single nucleotide polymorphisms [12] have been attempted. Despite these successes, oligonucleotide analysis by MALDI-MS has been limited primarily by the low ion abundances of larger oligonucleotides.…”
mentioning
confidence: 99%
“…A modification of SBE using tagged ddNTPs could make the difference easier to detect. 76 Another approach is to use a combination of ddNTPs and dNTPs for SBE reaction. The combination of the ddNTPs and dNTPs is made such that one allele stops at the polymorphic site, the other allele stops at one or few bases downstream.…”
Section: Identification Of Products By Mass Spectrometrymentioning
confidence: 99%
“…Whereas several MALDI-TOF MS-based methods have been introduced for genotyping SNPs, the primary strategy has been to generate SNP-containing products through primer extension for MS analysis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Haff and Smirnov invented a PinPoint assay based on the annealing of a primer to the 5′-end upstream of the target polymorphic site (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…This mass overlap also affects the efficiency and accuracy of the analysis of a number of polymorphic sites using multiple primers in any primer extension-based assay. Additional masses added to the ddNTPs can overcome the original mass stringency by shifting the mass of the extended primer (20,21). However, this still demands high instrumental resolution to resolve small mass changes involved in base substitutions, e.g., the 9 Da mass difference between an A and a T.…”
Section: Introductionmentioning
confidence: 99%